2010
DOI: 10.1002/cbdv.200900305
|View full text |Cite
|
Sign up to set email alerts
|

Protein‐Engineering Study of Contribution of Conceivable D‐Serine Residues to the Thermostabilization of Ovalbumin under Alkaline Conditions

Abstract: During storage of shell eggs, an egg-white protein, ovalbumin is converted into a molecular species with higher thermostability (Delta T(m)=8 degrees), which is named as S-ovalbumin. Since the pH of egg white is raised to 9.5 in that process, particular chemical modifications could occur. Although any evidence for relationship between chemical modifications and the thermostabilization had not been established, our X-ray crystallographic model for S-ovalbumin demonstrated that three serine residues (S164, S236,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Later, it was discovered that there are in fact two intermediate forms which both have one isomerized serine, i.e. Ser-164 or Ser-320, while Sovalbumin contains both serines in their isomerized form (Ishimaru, Ito, Tanaka, & Matsudomi, 2010;Takahashi, Maeda, Yamasaki, & Mikami, 2010).…”
Section: Egg Characterizationmentioning
confidence: 99%
“…Later, it was discovered that there are in fact two intermediate forms which both have one isomerized serine, i.e. Ser-164 or Ser-320, while Sovalbumin contains both serines in their isomerized form (Ishimaru, Ito, Tanaka, & Matsudomi, 2010;Takahashi, Maeda, Yamasaki, & Mikami, 2010).…”
Section: Egg Characterizationmentioning
confidence: 99%
“…It has been suggested that the S-ovalbumin contains d-Ser residues and these residues may contribute the thermostability of the protein [14,15]. We demonstrated the presence of d-Ser residues in ovalbumin using a technique combining deuterium labeling of amino acids and LC-MS/MS.…”
Section: Discussionmentioning
confidence: 82%
“…All mutant plasmids were prepared using the QuickChange PCR mutagenesis kit (STRATA-GENE, CA, USA), as described previously [15].…”
Section: Production and Purification Of Recombinant Ovalbuminmentioning
confidence: 99%
See 1 more Smart Citation
“…For SR inhibition assay using eluted fractioned, 5 µl and 7 µl of eluted fraction from pull down assay was used. For SR inhibition assay using purified compound madecassoside (MDS), 5,10,20,30,40,50,80, 100 µM of MDS was used. IC50 value for madecassoside was calculated using GraphPad Prism 7.…”
Section: Spr Based Screening Of Plant Extractsmentioning
confidence: 99%